Pengaruh Motivasi dan Kepuasan Kerja Terhadap Kinerja Guru SMA Negeri 6 Halmahera Utara Maluku Utara - Feby Angriawan Latumanase; Irwin Ananta Vidada (Syntax Corporation Indonesia, 2023)
Based on the 2022 Teacher Performance Assessment (PKG) as evidenced by the 2022 Teacher Competency Test, it explains that the results of the competency test for teachers, especially high school teachers in North Maluku Province with an average of 44.79, are considered low. SMA Negeri 6 Halmahera Utara as one of the best high schools in North Maluku Province is of course one of the schools that has low teacher performance. Even the students admit that the teachers of SMA Negeri 6 North Halmahera really teach in accordance with their duties and responsibilities, but there are a number of things that do affect teacher performance which are thought to be caused by a lack of motivation and job satisfaction in completing their assignments. The purpose of this study was to determine the effect of motivation and job satisfaction on teacher performance at SMA Negeri 6 Halmahera Utara, North Maluku. The research method that the author uses is the Quantitative Method by using a questionnaire on 30 teachers at SMA Negeri 6 Halmahera Utara, North Maluku. From the results of the study it was found that there is a positive relationship between motivation and teachser performance, job satisfaction and teacher performance.